Factors Affecting Firm Value with Financial Performance as the Intervening Variable - Caroline Vania Hartono; Stephana Dyah Ayu Ratnaningsih (Soegijapranata Catholic University, 2024)
This study aims to find evidence of the influence of corporate social responsibility disclosure and audit quality on firm value with financial performance as an intervening variable. The sample of this study consists of 206 companies listed in the PROPER Assessment by the Ministry of Environment and Forestry for the years 2019-2020 and 2021-2022 and also listed on the Indonesia Stock Exchange during the years 2019-2022. Sample selection was conducted using purposive sampling, resulting in 143 companies being sampled. The data used in this study are secondary data. Hypothesis testing was conducted using path analysis method using SPSS version 21 and Sobel Test. The results of this study prove that: 1. Financial performance can mediate the influence of Corporate Social Responsibility on Firm Value. 2. Financial performance can mediate the influence of Audit Quality on Firm Value.